1998
DOI: 10.1016/s0014-5793(98)00400-1
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐linking and mutational analysis of the oligomerization state of the cytokine macrophage migration inhibitory factor (MIF)

Abstract: The structure of the cytokine MIF has been investigated by X-ray crystallography, NMR, and biochemical methods with conflicting results regarding the structural and functional oligomerization state of this protein. Determination of the oligomeric state(s) is important for understanding more precisely the molecular mechanism of MIF action. To address this issue, we performed cross-linking of human and mouse MIF and selected mutants by various methods and analyzed the oligomerization by SDS-PAGE and gel filtrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
48
0
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 43 publications
3
48
0
2
Order By: Relevance
“…Recombinant His 6 -tagged PMIF and huMIF elute at apparent molecular masses of 30 and 22 kDa in size exclusion chromatography, and these sizes are both consistent with a dimeric form in solution. Until (37), the His 6 tag does not appear to affect oligomerization. However, a more in-depth study is required to determine the exact oligomerization status of PMIF in solution.…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant His 6 -tagged PMIF and huMIF elute at apparent molecular masses of 30 and 22 kDa in size exclusion chromatography, and these sizes are both consistent with a dimeric form in solution. Until (37), the His 6 tag does not appear to affect oligomerization. However, a more in-depth study is required to determine the exact oligomerization status of PMIF in solution.…”
Section: Discussionmentioning
confidence: 99%
“…X-ray crystallography studies indicate that MIF exists predominantly in a trimeric form [36,37], whereas NMR [21], sedimentation velocity [24], size exclusion chromatography [22], and solution crosslinking studies [23] indicate that MIF also may exist in dimeric and monomeric forms. However, recent studies reexamining the molecular size and hydrodynamic properties of MIF in solution suggest that it exists in solution predominantly (>95%) as a trimer, which sediments with a sedimentation coefficient of 3.1S [38].…”
Section: Analytical Ultracentrifugation Analysis Of the Ph-dependent mentioning
confidence: 99%
“…1B). Although MIF crystallizes as a trimer [19], experimental studies employing NMR spectroscopy [21], size-exclusion chromatography [22], chemical cross-linking [23,24], and analytical ultracentrifugation support the existence of dimeric and monomeric forms in solution [24].…”
mentioning
confidence: 99%
“…However, it is currently not known whether this represents the true, physiological state of MIF protein, as studies have suggested bioactive MIF monomers or dimers (Mischke et al 1998). Each monomer of MIF is known to be composed of the following: two antiparallel -helices ( 1 and 2) and six strands ( 1-6).…”
Section: Mif Proteinmentioning
confidence: 99%